ANALISIS PENINGKATAN PROFITABILITAS SEBELUM DAN SESUDAH PENGGUNAAN E-COMMERCE DAN SISTEM INFORMASI AKUNTANSI PADA CV. TIGA PERKASA ABADI - Putri, Faradila Sepiana; Purwanti, Meilani (Journal of Information System, Applied, Management, Accounting and Research, 2025)
The purpose of this research is to see how the use of e-commerce and accounting information systems function in increasing the company's profitability. The method used in this research is qualitative. Research data were obtained through interviews with the company's PIC, direct observation of business processes and financial management, and documentation. Information analysis was carried out using information reduction techniques, information presentation, and conclusion drawing. According to this study, the use of e-commerce helps companies expand market reach, improve operational efficiency, and drive sales volume growth. In addition, the implementation of an integrated accounting information system has improved the accuracy and timeliness of financial reporting, making it easier for management to analyze financial performance and make strategic decisions. The findings of this study indicate that the synergistic use of e-commerce and accounting information systems can increase company profits. The theoretical implication of this study is to enrich the literature on the utilization of digital technology to improve corporate financial performance.